Growing minds cognitive development in early childhood - Elkind, David, 1931-; Davidson, Frances W.; Davidson, John M.; Davidson Films (San Luis Obispo, CA: Davidson Films, 1995)
This video compares theories of Lev Vygotsky and Jean Piaget regarding the cognitive development of young children. Reasoning, visual perception and the use of language are examined by Dr. David Elkind to show how children's intellectual abilities change over time
Producer, Frances W. Davidson ; director, John M. Davidson
Host: David Elkind ; narrator, David Elkind
Keywords: Child development; Child psychology; Cognition in children